Physical And Mechanical Characteristics Of Charcoal, Sawdust And Sugarcane Bagasse As Solid Fuel Materials - Abdulkareem, S.; Badejo, H. A.; Ahmed, I. I.; Adebisi, J. A.; Taiwo, Y.; Ajiboye, T. K.; Abdulrahim, A. T. (Journal of Engineering and Technology (JET), 2017)
This paper reports on the physical and mechanical characteristics of briquettes produced from charcoal, sawdust and sugarcane bagasse using molasses with sodium silicate as binders. Charcoal, sawdust and sugarcane bagasse were mixed in respective ratio of 20:20:60, 20:30:50, 20:40:40, 20:50:30 and 20:60:20. The briquettes were produced using Budenberg dial gauge compression machine, with pressure of 64 MPa at 120 seconds dwell time. Physical properties (relaxation ratio, compaction ratio and shattering index) and mechanical property (compressive strength) of the produced briquettes were investigated. Results show that briquette with sample composition of 20:30:50 has better physical properties with relaxation ratio of 1.562, compaction ratio of 7.573 and shatter index of 99.6%, while sample with ratio 20:40:40 has highest compressive strength of 55.43 kN/m2.